IMPLEMENTASI LESSON STUDY PADA MATA KULIAH ANATOMI FISIOLOGI MANUSIA UNTUK MEMPERSIAPKAN CALON GURU YANG BERKUALITAS - Budhi Utami; Endah Apriani (Universitas Sebelas Maret, 2014)
Implementation of Lesson Study in Biology Education Program UNP Kediri studies have been initiated since the academic year 2012/2013. In the first, conducted for the course LS SPT and SPH on the second level of the 3rd semester. Subsequent semester applied for the course LS Basic Genetics and Plant Taxonomy.Research experience as a lecturer on the implementation of the Basic Genetic models LS is advantageous because the Plan stage, preparation of syllabi and lecture plan lecturer models got a lot of feedback about the matter, both the content and linkage with the subject matter in the next semester (Advanced Genetics), being on stage Do lecturer models aided by the observer observing student participation during the lecture. At this stage of the model describes the reflection lecturer findings obtained during learning such as discipline, willingness to learn, active participation in the discussions and in the process, and input from the faculty observer findings reinforce the model, so the lack of sub-optimal learning outcomes can be immediately known, and find a way exit.The research was conducted in the course of Human Anatomy Physiology Female Reproductive System on the theme, with a sample of students of Biology Education Program UNP Kediri of 35 students, the academic year 2013/2014. The findings obtained in cycle 1 by lecturers models of group 3A is less student discipline, willingness to learn, an increase from prior LS implemented, active student better than before although not comprehensive LS only about 40% of the number of students (35 people). In cycle 2, there was an increase in time classroom discipline, a willingness to learn increases seen from the test results of the evaluation of learning is on the first cycle increased 58.7 to 71.5 (up 36 %) and students are also more active in both the discussion and the question and answer after the presentation by the group renderer. Keywords : Implementation, Lesson Study